2009
DOI: 10.1128/ec.00330-08
|View full text |Cite
|
Sign up to set email alerts
|

Global Gene Expression Analysis during Germination in the Chytridiomycete Blastocladiella emersonii

Abstract: Blastocladiella emersonii is an aquatic fungus of the Chytridiomycete class. During germination, the zoospore, a motile nongrowing cell, goes through a cascade of morphological changes that culminates with its differentiation into the germling cell, capable of coenocytic vegetative growth. Transcriptome analyses of B. emersonii cells were carried out during germination induced under various environmental conditions. Microarray data analyzing 3,563 distinct B. emersonii genes revealed that 26% of them are diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 49 publications
0
8
0
9
Order By: Relevance
“…Transcriptome studies with N. crassa, Fusarium graminearum, and Ustilago maydis have been performed using spores germinated in minimal (N. crassa and U. maydis) or full (F. graminearum) media in (partly shaken) suspensions, with no permanent surface contact of the spores (17,18,19). Blumeria microarray-based studies with germinated conidia forming infection structures, including haustoria, on the surface and within host epidermal cells have focused mainly on transcriptomic changes related to metabolic pathways, such as lipid degradation, glycolysis, pentose phosphate pathway, and amino acid biosynthesis (20,21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptome studies with N. crassa, Fusarium graminearum, and Ustilago maydis have been performed using spores germinated in minimal (N. crassa and U. maydis) or full (F. graminearum) media in (partly shaken) suspensions, with no permanent surface contact of the spores (17,18,19). Blumeria microarray-based studies with germinated conidia forming infection structures, including haustoria, on the surface and within host epidermal cells have focused mainly on transcriptomic changes related to metabolic pathways, such as lipid degradation, glycolysis, pentose phosphate pathway, and amino acid biosynthesis (20,21).…”
mentioning
confidence: 99%
“…Transcriptome profiling analyses during germination have been published for N. crassa (17), the saprotrophic chytridiomycete Blastocladiella emersonii (18), and the wheat pathogen F. graminearum (19). These studies revealed major changes of gene expression patterns starting already during the pregermination swelling stage.…”
mentioning
confidence: 99%
“…In contrast, data revealed that most genes involved in signal transduction showed the same expression profile during the initial stages of germination with all the inducers investigated. These results indicate that the same signaling pathways are activated irrespective of the initial stimulus triggering germination (29).…”
mentioning
confidence: 67%
“…The expression profiles of 530 genes differentially expressed during (29) and sporulation (this work) of B. emersonii were compared through clustering analysis using the algorithm K-means. Data revealed that approximately 95% of the genes analyzed are inversely regulated between these two differentiation stages (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation